Literature Is Us and We Are Literature: Global and Universal Perspective - Classen, Albrecht (International Journal of Culture and History, 2023)
This paper takes into view literature on a global scale and from throughout time to investigate what we can say about its general and specific relevance for human society. The issue raised here pertains not only to the relevance of literature per se, but specifically to the question of how it relates to us as human beings, defining us in endless ways. In order to illustrate the central points addressed in this paper, numerous examples from the Middle Ages to the modern world are drawn from, such as Hartmann von Aue’s Der arme Heinrich (ca. 1190), Don Juan Manuel’s El Conde Lucanor (1335), Bertolt Brecht’s ballads, and Robert Frost’s modern poetry. The conclusion emphasizes that the critical function of literature in all human societies cannot be overestimated. At the risk of preaching to the converted, here we are confronted with the ultimate challenge in the Humanities once again. Insofar as literature has always mirrored, or engaged with, the fundamental issues in human life, we can establish its function as life-determining in philosophical, religious, political, ethical, or moral terms.